Are state-owned banks less efficient? A long- vs. short-run Data Envelopment Analysis of Chinese banks. (2nd July 2008) - Cooper, W.W.; Ruefli, Timothy W.; Deng, Honghui; Wu, Jun; , Zhongyi Zhang
This paper applies Data Envelopment Analysis (DEA) to determine relative efficiencies of state-owned and joint stock banks in Chongqing, China, during the period 1996?2000. A distinction is made between long- and short-run efficiencies and inefficiencies to allow for the fact that joint stock banks are relatively new to China have more modern management and access to international finance markets while state-owned banks generally use government funding. Using Mann?Whitney rank order statistics produces results in favour of joint stock banks in the short-run but not in the long-run. A relatively new way of distinguishing between long- and short-run performances is utilised that avoids the need for identifying lengthy time periods and data associated with long-run performances.